Effective management of agriculturall and from the state land in the Shumen region - Varbanov, Dimitar (Leadership, Society, Strategic Visions, 2021)
The Bulgarian state is the largest owner of agriculturall and son theterritory of Shumen Province. The State Land Fund is effectively managed throught heright choice of different time frames of short, medium and long-term leases inorder to achieve anoptimalsolution. The results, such as abid price and anaveragerent price, are very important and the Income Amount from ownership and control of agricultural land sin the republic an budget is directly dependent up on them. The results of analyzing the allocation of state farmland for previous business years should be the basis for a decision-making and the follow-up tender procedures.